Polymorphisms of the methylenetetrahydrofolate reductase gene (C677T and A1298C) in the placenta of pregnancies complicated with preeclampsia. (3rd July 2015) - Chedraui, Peter; Andrade, Mariela E.; Salazar-Pousada, Danny; Escobar, Gustavo S.; Hidalgo, Luis; Ramirez, Cecibel; Spaanderman, Marc E. A.; Kramer, Boris W.; Gavilanes, Antonio W. D.
Abstract: Background : Preeclampsia has been related to single-nucleotide polymorphisms (SNPs) of the methylenetetrahydrofolate reductase (MTHFR) gene; however, data regarding the placenta are still lacking. Objective : To determine the frequency of C677T and A1298C SNPs of the MTHFR gene in the placenta of preeclamptic pregnancies and healthy controls. Methods : Genotyping of C677T and A1298C polymorphisms of the MTHFR gene using RFLP-PCR was performed to the placenta of 100 gestations ( n  = 50 complicated with preeclampsia and n  = 50 normal controls matched for parity and maternal age). Results : Gestational age at birth and neonatal and placental weight were significantly lower in women with preeclampsia as compared to controls. The TT genotype of the C677T polymorphism was threefold more prevalent in preeclamptic placentas as compared to the placenta of controls (24.0% versus 8.0%, p  = 0.001). Upon pooled analysis ( n  = 100), placental and neonatal weights were significantly lower in placentas displaying this genotype (TT, C677T) as compared with the CC genotype. Conclusion : This study found that the frequency of the TT mutant genotype of the C677T polymorphism was higher in the placenta of pregnancies complicated with preeclampsia. There is a need for further research in this matter.